Implementation of Rice ATM Management for Zakat Distribution to Mustahiq in BAZNAS Jombang Indonesia - Awal Amarudin, Amin; Annisa Oktaviani, Putri (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2024)
Rice ATMs are a means of facilitating the distribution of zakat without directly involving the brains of mustahiq and muzzaki. The urgency of rice ATMs is to help the poor get their basic needs in the form of rice, without good management this goal will not be achieved. This research aims to determine the implementation of Rice ATM management at BAZNAS Jombang, the problems faced in the Rice ATM program and their implications. This research uses a qualitative approach where data is obtained through observation, interviews and documentation, while data checking is carried out through data triangulation. The research results show that, firstly, the implementation of Rice ATM management at BAZNAS Jombang is good according to George R. Terry's theory. Second, the problems faced are divided into 5 parts, including problems related to rice ATM machines, fundraising strategies, UPZ limitations, Jombang BAZNAS administrators, and mustahiq. Third, the implications of the presence of a rice ATM in the courtyard of the Great Jombang Mosque have a significant impact on mustahiq and muzzaki. These implications include increased accessibility for mustahiq in fulfilling their basic needs, heightened awareness among muzzaki regarding their social responsibilities, and an overall enhancement in the perception of zakat distribution as a transparent and efficient system.